The principle of sincerity in French budgetary law - Zawadzka-Pąk, Urszula (Studia Iuridica Toruniensia, 2026)
While the budgetary principles of annuality, unity, universality, and specificity are well established in the Polish legal system and have been the subject of a relatively large number of studies in Polish doctrine, the situation is completely different in the case of the principle of sincerity (fr. le principe de sincérité), on which there is no comprehensive scientific study in Polish. Therefore, in order to fill this gap in the literature, the aim of this article is to explain the essence and legal basis of the principle of sincerity in French budgetary law. To achieve this goal, a dogmatic method was used, analysing both the content of the law itself, the views of the doctrine and the case law of the French Constitutional Council, as well as the reports of the Court of Auditors.